2020
DOI: 10.1007/s13534-020-00171-8
|View full text |Cite
|
Sign up to set email alerts
|

Freeform 3D printing of soft matters: recent advances in technology for biomedical engineering

Abstract: In the last decade, an emerging three-dimensional (3D) printing technique named freeform 3D printing has revolutionized the biomedical engineering field by allowing soft matters with or without cells to be printed and solidified with high precision regardless of their poor self-supportability. The key to this freeform 3D printing technology is the supporting matrices that hold the printed soft ink materials during omnidirectional writing and solidification. This approach not only overcomes structural design re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 85 publications
(254 reference statements)
0
65
0
Order By: Relevance
“…[19,29] In some liquid-in-liquid 3D printing methods, the miscibility between the phases is shown to limit printing precision and inhibit adhesion between printed features. [1] However, not every immiscible water-oil interface allows for formation of a smooth stream for the injected surfactant solution such as the case with castor oil or silicone oil. For the oil to be effective in this 3D printing approach, it requires certain surface activity with the aqueous surfactant solutions to be able to produce gellike aggregates formed using surfactant self-assembly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19,29] In some liquid-in-liquid 3D printing methods, the miscibility between the phases is shown to limit printing precision and inhibit adhesion between printed features. [1] However, not every immiscible water-oil interface allows for formation of a smooth stream for the injected surfactant solution such as the case with castor oil or silicone oil. For the oil to be effective in this 3D printing approach, it requires certain surface activity with the aqueous surfactant solutions to be able to produce gellike aggregates formed using surfactant self-assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Printing and patterning programmable soft materials into predefined 3D constructs for biomedical applications is a challenging DOI: 10.1002/marc.202100445 task due to the weak mechanical strength of soft materials as well as low structural stability of constructs. [1,2] Traditional layer-bylayer 3D printing, which is typically based on direct extrusion, has been adopted as the main approach for patterning of soft materials. [3][4][5][6] However, most soft materials are not widely applicable to current 3D printing techniques, since they must possess specific physicochemical properties (i.e., rheological behavior and crosslinking mechanisms) during printing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though 3D-printing materials are known for their inability to properly mimic soft biological tissues such as skin tissues, the recent development of a new technique called freeform 3D printing has revolutionized the field by allowing soft matters such as hydrogels and silicone elastomers to be printed [ 28 ]. The use of such techniques could improve our skin model; they would likely make the skin addition on our models more time-efficient, and by opening the door to other soft materials, they could provide an improved haptic representation of living animal skin, particularly useful for sutures.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, a supporting bath-assisted 3D printing (SBP) technique where ink is dispensed inside a gel or a suspension with thixotropy is noteworthy. Under shear forces, the viscosity of a gel or a suspension becomes of low viscosity, enabling the ink dispensing, and it returns to a high viscosity when the shear force is released, maintaining the printed form 17 . Since the SBP is able to overcome not only the restricted ink viscosity range but also the drying problem during prolonged printing in extrusion-based 3D printing in the air-interfaced environment, several studies over the past five years have shown the feasibility of complex tissue fabrication 18 – 24 .…”
Section: Introductionmentioning
confidence: 99%